2021
DOI: 10.3389/fimmu.2021.673405
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Circadian Rhythms Dysregulate Inflammation in Ageing: Focus on Leukocyte Trafficking

Abstract: Leukocyte trafficking shows strong diurnal rhythmicity and is tightly regulated by circadian rhythms. As we age, leukocyte trafficking becomes dysregulated, contributing to the increased systemic, low-grade, chronic inflammation observed in older adults. Ageing is also associated with diminished circadian outputs and a dysregulation of the circadian rhythm. Despite this, there is little evidence to show the direct impact of age-associated dampening of circadian rhythms on the dysregulation of leukocyte traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…The activation and transport of associated leukocytes and cytokines also exhibit strong circadian rhythms and are tightly regulated by circadian rhythms. Dysregulation of circadian rhythms has been reported to directly affect leukocyte trafficking as a way to influence inflammation and immune-mediated inflammatory diseases ( 29 ), including AS. For example, disruption of circadian rhythms has been observed to significantly increase the content of damaged macrophages and increase inflammatory and oxidative stress markers in the vascular wall of AS mice ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activation and transport of associated leukocytes and cytokines also exhibit strong circadian rhythms and are tightly regulated by circadian rhythms. Dysregulation of circadian rhythms has been reported to directly affect leukocyte trafficking as a way to influence inflammation and immune-mediated inflammatory diseases ( 29 ), including AS. For example, disruption of circadian rhythms has been observed to significantly increase the content of damaged macrophages and increase inflammatory and oxidative stress markers in the vascular wall of AS mice ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, organ-specific phenotypic reprogramming occurs during ageing, implicating interaction of reverse-transmigrated neutrophils within the lung, which primes these cells for an activated phenotype responsible for the induction of remote organ damage [ 80 ]. Of note, ageing is also associated with disturbances in circadian rhythms, leading to imbalances in immune cell responses [ 81 ], and likewise, disturbed circadian rhythmicity due to genetic targeting of BMAL1 leads to premature ageing [ 82 ]. As for the cell-intrinsic maturation and ageing, aged neutrophils feature high CXCR4 expression, which mediates their clearance within the bone marrow [ 40 , 49 ].…”
Section: Principles and Regulatory Factors Affecting Immune Phenotype...mentioning
confidence: 99%
“…50 It is important to note that influence of the circadian clock on inflammatory mediators is bidirectional: Although circadian disruption is known to promote chronic inflammatory and metabolic diseases, inflammation can also directly affect the circadian clock. 51 In fact, the pro-inflammatory cytokine TNF-α has been shown to suppress the expression of clockcontrolled genes. 52 The impact of severe inflammatory response, called the cytokine storm syndrome (CSS), on COVID symptoms and fatality is well documented and has been proposed to be mediated by NOD-like receptor 3 (NLRP3) inflammasome activation.…”
Section: Innate Immunity and The Circadian Clockmentioning
confidence: 99%
“…have shown that the Bmal1 gene is expressed in macrophages and can regulate the timing of genes expressed in response to inflammatory activation, partially via the regulation of the transcription of REV‐ERBα/β and enhancer RNAs (eRNA) in macrophages using Bmal1 −/− cells and mouse models 50 . It is important to note that influence of the circadian clock on inflammatory mediators is bidirectional: Although circadian disruption is known to promote chronic inflammatory and metabolic diseases, inflammation can also directly affect the circadian clock 51 . In fact, the pro‐inflammatory cytokine TNF‐α has been shown to suppress the expression of clock‐controlled genes 52 .…”
Section: Links Between Circadian Clock and Covid‐19mentioning
confidence: 99%